Protection of the High Seas and Marine Protected Areas - Sercan Reçber (Public and Private International Law Bulletin)
Significant pollution and destruction have taken place in the oceans as a result of human activities. Human-induced pollution in this vast ecosystem, destruction and dimensions of climate change pose a great danger to ocean life and thus life on earth. It is inevitable that this effect will increase unless the necessary measures are taken. The concept of protection of the marine environment has undergone a significant transformation in the last three decades. An approach that includes a broader conservation approach, takes into account the unique characteristics of each marine area, and aims to protect the entire marine ecosystem, is adopted. Although it is seen that the states are taking protective measures for these areas with the regulations for the protection of the environments of their own marine territory, these measures appear to be insufficient in offshore areas outside the states’ national jurisdictions. When it comes to solving these problems for marine life, marine protection areas are important in terms of fulfilling this function, although their scope and size differ. Marine protection areas are considered by scientists as suitable tools for the protection of sensitive ecosystems in the case of appropriate planning and effective management of the protected area, taking into account the characteristics of the marine area concerned. The creation of much more effective protection regimes on the high seas which are the world’s largest communal area, stands before humanity as an urgent problem, considering the current and future destruction going on.